Web-Based Student Grade Management Information System - Indri Anugrah Ramadhani; Sahiruddin Sahiruddin; Muhamad Ali Kasri; Soleha Alhamid (JTP - Jurnal Teknologi Pendidikan, 2025)
Digital transformation is pushing schools to adopt efficient academic information systems, but many schools in 3T areas including SMK Muhammadiyah Aimas still manage grades manually, making them prone to input errors, data duplication, and slow academic recap and reporting processes. This situation shows how important it is to find a systematic way to make value management more accurate, efficient, and open. This research aims to develop and evaluate a web-based system for managing value, designed to meet the needs of vocational schools in a limited context. Using a Research and Development (R&D) approach, the developed system integrates master data management, daily values, midterm exams, final exams, attendance, and automatic final grade calculation. The test results show that all features function according to specifications, while expert validation places the software aspect in the "very good" category. Usability testing by teachers yielded a score of 93%, indicating a high level of ease of use, satisfaction, and utility. The novel contribution of this research is the creation of a web-based value system that amalgamates value and attendance automation within the framework of 3T schools, a subject that remains infrequently examined. The study's limitations include the absence of API integration and its focus on a single school for evaluation. Nevertheless, this system has important implications for improving teachers' work efficiency and accelerating school digitalization in 3T.